The meaning of “total pain” in the context of living and dying with dementia - Field-Richards, Sarah Elizabeth; Bramley, Louise; Collins, Jemima; Cowley, Alison; Harwood, Rowan (Frontiers in Sociology, 2025)
BackgroundGlobally, there are 55 million people living with dementia (PLWD). PLWD have an uncertain prognosis. Most are approaching the end of life but are not overtly or immediately dying. Contemporary approaches to dementia care therefore promote the need to live and die well with dementia. Pain is highly prevalent but difficult to manage in PLWD. Originating in palliative care, “total pain” conceives of pain holistically, incorporating biological, psychological, social and spiritual elements. Pain management in dementia care tends to be pharmacologically focused. Total pain therefore offers an alternative approach—one consistent with person-centred philosophy underpinning contemporary dementia care. Due to important differences, concepts cannot simply be extrapolated from cancer-related to dementia-related palliative care however. Dementia-specific approaches are needed and require exploration.Description and objective of the analysisThe objective of this paper is to explore the meaning of total pain in the context of living and dying with dementia, and its utility and implications for person-centred dementia care. Using a palliative care framework and existing literature, we critically consider the bio-psycho-socio-spiritual impact of dementia, to explore how total pain might manifest and be experienced in this context.Findings and interpretationWe highlight the complexity, nuance and socially contingent nature of the impact of living and dying with dementia. We challenge binary understandings of “continuity or loss” (e.g., of identity, relationships), and totalising “loss” discourses, demonstrating that more subtle, varied and hopeful outcomes are possible. The way that the impact of dementia is articulated and understood has implications for the experience and management of total pain. The deficit-orientation of “total pain” paradoxically risks its perpetuation. A balanced understanding of dementia’s impact (acknowledging both continuity and loss, alternatives and socially constructed aspects) better reflects the realities of dementia and creates new possibilities for supportive care practices to improve pain management and quality of life.Conclusion and implications for practiceApplied to dementia care, “total pain” should be located within a critical context, emphasising complexity, contingency and nuance. The holistic focus of “total pain” should be extended to incorporate balanced consideration of “painful” and “functional” experience. We introduce a balanced model of total pain incorporating a dual focus on “pain” and “personhood” within a critical context, to facilitate translation to practice. There is a need to develop evidence-based supportive interventions in each domain of total pain, to support a balanced approach to total pain management in dementia care.